Pelembagaan Beban Administratif pada Regulasi Pendirian Rumah Ibadat di Indonesia - Wijaya, Calvin Nathan; Prasojo, Eko (JPAP: Jurnal Penelitian Administrasi Publik, 2023)
After five decades of implementing regulations on the construction of places of worship, the debates surrounding the policy have never ceased. The regulation has encountered religious entities in the form of administrative burdens through various requirements imposed on them to limit the construction of places of worship. This research aims to examine the origins of the burdens contained in the regulation, namely Joint Regulation of the Minister of Religion and the Minister of Home Affairs 8 & 9/2006, with an emphasis on why these administrative requirements exist and continue to exist today. By following process-tracing methods, this research found that this administrative burden existed and continues to exist due to past disputes between Muslims and Christians which were triggered by Christian missionary activities which culminated in attacks on churches in several areas. This has been traumatic for both parties and sparked persistent suspicion between the two groups. This research proposes that this phenomenon can be called "institutionalization of administrative burden" which is a form of behavior based on traumatic feelings that the state legitimizes due to past conflicts. Some indications institutionalizing these burdens result in negative behavior patterns, which means the government needs to consider changing or improving the regulation carefully.